Analisa Yuridis Penunjukan Pejabat Wali Kota Sukabumi pada Masa Transisi Pemilu Serentak Nasional pada Tahun 2024 - A Rijalullah Kusumah Cakra; Agus Rasyid Chandra Wijaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Simultaneous regional elections resulted in the vacancy of leaders in various cities, including the city of sukabumi, therefore the appointment of officials (Pj) to fill the vacancy of the position of regional head of the city mayor until the election of regional heads in the simultaneous regional elections in 2024. however, the appointment of PJ is problematic because it is not in line with the spirit of democracy. This research examines and analyzes related to the appointment of the PJ of the mayor of Sukabumi which is not in line with the principles of democracy, therefore the researcher raises the formulation of the problem among them. First, is the appointment of the acting mayor of Sukabumi in accordance with the principles of democracy? Second, whether the appointment of the acting mayor of the city of Sukabumi is in accordance with the Constitutional Court Decision Number 67/PUU-XIX/2021 and MKRI Decision Number 15/PUU- XX/2022. This research uses an analytical descriptive method with a normative juridical approach, in which data and information are analyzed normatively. The results showed that the appointment of the Pj mayor of Sukabumi did not involve the DPRD as a representation of the people of Sukabumi so that it can be said that it does not fulfill the principles of democracy and heed the Constitutional Court Decision Number 67/PUU-XIX/2021 and MKRI Decision Number 15/PUU- XX/2022 which mandates the making of implementing regulations to make PJ appointments without heeding the principles of democracy which are the spirit of the struggle of the Indonesian nation and the people of the city of Sukabumi.